Suplementos múltiplos na terminação de bovinos de corte em pastejo no período das águas - Koscheck, Jefferson Fabiano Werner (2013)
We evaluated the providing supplements multiple relationships with different TDN: CP on ruminal pH, ruminal ammonia nitrogen concentration, intake and digestibility, nitrogen balance, microbial efficiency, performance, economic analysis and ingestivo behavior for beef cattle on Marandu pasture during the rainy. Supplements were comprised of a mineral mix, ground corn grain, soybean hulls, roasted soybeans and urea:ammonium sulfate. Mineral mix and supplements were supplied at levels 800, 1600 and 2400 g/animal/day, containing 500, 1000 and 1500 g of TDN, respectively, named S500, S1000 and S1500, with supplemental crude protein (CP) fixed at 300 g animal/day for all supplementing strategies. We used four crossbred rumen fistulated steers with average weight of 512 kg distributed in 4x4 Latin square design into four paddocks with 0.25 ha each to evaluate the nutritional characteristics. For performance evaluation 20 young bulls with 24 months of age and average initial body weight of 418.48 kg were used, the animals were distributed in total randomized design with four supplements and five replicates. Supplementation was enough to increase the nitrogen concentration in the rumen in about 63% four hours after supplementation compared only mineral mix suply (P<0,05). Supplementation did not alter the intake and digestibility of dry matter or organic matter (P>0,05), although the supplement with 1500 g TDN promoted greater intake of non-fibrous carbohydrates, when compared with the other supplementation strategies (P<0,05). Supplementation with 300 g CP/animal/day promoted higher intake of crude protein and nitrogen and greater concentrations of nitrogen in the urine and in the serum (P<0,05), however did not change nitrogen balance (P>0,05). Providing multiple supplements provided better microbial efficiency (P <0.05), higher by 39% compared to non-supplemented animals. The weight gain of the animals was 0.671, 0.914, 1.071 and 0.960 kg / day, respectively, for the MM supplements, S500, S1000 and S1500 verifying statistical difference by only orthogonal contrast between the MM supplement and other supplements (P <0.05). The increased level of supplementation, with a consequent increase in the supply of extra NDT was not able to generate positive response in weight gain between the supplemented animals (P> 0.05). A common feature among the supplements was the amount of CP supplied to each animal (300 g), which was probably the key point for superior performance compared to non-supplemented animals (P <0.05). The best economic return was obtained when supplementation level of 1.6 kg / animal / day which represents approximately 0.4% of body weight of the animal. For the variables related to the diurnal ingestive behavior, there was difference in the control group compared to time supplemented to the trough (P <0.05). It was concluded that providing multiple supplements for finishing cattle during the summer that provides 300 grams of CP / animal / day with different relationships TDN: CP provide positive effects on concentration of nitrogen in the rumen, microbial efficiency, performance and economic analysis.